The organixational factors and demographical variables affecting ethical perceptions of employees in business life - Aksoy, Filiz (My University, 2003)
Bu çalışmanın amacı iş hayatındaki ahlaki anlayışın organizasyonel faktörlere (misyonun varlığı, ahlaki ilkelerin varlığı, etik eğitimin varlığı, organizasyon boyutu, hiyerarşideki kariyer durumu, iş memnuniyeti ve işe bağlılık) ve demografik etkenlere (cinsiyet, yaş, eğitim durumu, eğitim alanı) bağlı olarak değişimi incelemektir. Çalışmanın temeli organizasyonel faktörler ve demografik etkenlerle ahlaki anlayış arasındaki ilişkiyi inceleyen araştırma sorularıdır. Çalışma iki ana bölümden oluşmaktadır. Birinci bölümde literatürden derlenen etik ve iş etiği konuları incelenmiştir. Ahlakla ilgili çeşitli teoriler, ahlaki karar verme metodolojileri, iş hayatında ahlaki karar vermeyi etkileyen faktörler, etkenler iş etiği açısından tartışılmıştır. Organizasyonel faktörler ve demografik etkenler olarak iki başlığa bölünmüştür. Faktörler ve etkenler yakın tarihte yapılmış araştırmalardan derlenmiştir. İkinci bölümde çalışanların etik anlayışını bu faktör ve etkenlere bağlı olarak ölçülmüştür. Literatürde bulunan anketler yardımıyla araştırma hipotezleri test edilmiştir. Test sonuçlarına göre dört önemli bulgu elde edilmiştir: Hiyerarşideki kariyer durumu açısından etik anlayış farklılık göstermiştir. Ayrıca demografik etkenlerden cinsiyet, yaş ve eğitim alanı açısında etik anlayış farklılık göstermiştir. Bu çalışma iş hayatında güncel bir konuyu analiz etmiştir. Araştırma bazı organizasyonel faktörler ve demografik etkenlere göre ahlaki anlayışta farlılık olduğu ispatlanmıştır. Bu açıdan, organizasyonların problemlerini çözümlemede bir yol gösterici olacaktır. Ayrıca, yöneticiler iş ortamının ahlaki boyutundan etkilenen hedef çalışan gruplarını belirleme konusunda fikir sahibi olabileceklerdir. Çalışmada kullanılan ve iş vakalarından oluşan anketin de yöneticilerin diğer etki faktörlerini incelemede faydası olacaktır. Sonuç olarak, Türk şirketlerinde gerçekleştirilen bu çalışma, konu ile ilgili alanlarda bir boşluğu doldurmuştur. The major objective of this study was to investigate the concept of ethical perceptions of business world according to the variations in organizational factors (presence of mission statement, presence of code of ethics, presence of ethical education, organizational size, career position in the hierarchy, job satisfaction and organizational commitment) and demographical variables (gender, age, educational major, educational level). The basis of the study was the research questions asking for significant relationship between ethical perceptions and organizational factors-demographical variables. The context of this study was made up of two parts. The first part explored the term ethics and business ethics as discussed in literature. Various theories related to ethics, methodologies in ethical decision making, major factors affecting ethical decision making in business life were gathered from the recent studies conducted by researchers. Factors and variables affecting ethical decision making were divided into two titles as organizational factors and demographical variables. Furthermore, in the second part of this study the relationship between variables and ethical perceptions of managers were investigated. With the use of a questionnaire developed, based on previous studies in literature the research, hypothesis were tested. According to the test results, four important conclusions were derived: Ethical perceptions vary with respect to career position in the hierarchy. In case of demographical variables, gender, age and educational major affect the variations in ethical perceptions of managers. This study has analyzed an important topic of business life discussed recently. The research proved the fact that there are differences in ethical perceptions of managers depending on some organizational factors and demographical variables. Therefore, it will be useful for the ethical management of related departments in business organizations and it will show a path to them in coping with ethical problems. The managers will have opinion on target groups of employees who are affected from unethical business environment. Furthermore, the questionnaire including the business scenarios may help the managers to access the ethical perceptions of employees through analyzing different factors. As a result, this research conducted in Turkish companies filled the gap in this area.
Keywords: İş Ahlakı